Diversity and conservation status of ungulates in the Mono Transboundary Biosphere Reserve, Togo (West Africa). Issue 3 (3rd July 2018) - Segniagbeto, Gabriel H.; Atsri, Komina H.; Assou, Délagnon; Koda, Koudzo D.; Amori, Giovanni; Decher, Jan; Dendi, Daniele; Luiselli, Luca
Abstract : Ecological data on ungulate mammals are poorly available for Togo (West Africa), also with regard to the populations inhabiting the various protected areas. To provide preliminary data on the ecology of Togolese ungulates, several field missions were carried out between September 2014 and August 2017 in the various ecological units considered as key areas for large mammals of the Mono Transboundary Biosphere Reserve (MTBR). MTBR, located along the Mono River, has several ecological units of varying sizes, with the Togodo Protected Areas Complex being the largest within the biosphere reserve (25, 500 ha). A total of 12 species belonging to four families were recorded on the basis of direct observations and/or signs of presence. These include: Tragelaphus eurycerus, Tragelaphus gratus, Tragelaphus phaleratus, Syncerus brachyceros, Kobus kob, Philantomba walteri, Cephalophus rufilatus, Cephalophus sylvicultor, Sylvicapra grimmia, Hippopotamus amphibius, Potamochoerus porcus, Phacochoerus africanus . Another species ( Kobus ellipsiprymnus ) has been reported from hunter surveys. The field sightings of ungulates were especially concentrated in the Togodo protected area complex, but also the smaller ecological units (such as the Afito pools, the Avéve forest and the Akissa forest) seemed to play an important role in consolidating the ecological functioning of th biosphere reserve. Indeed, groups of T. gratus T. phaleratus and H. amphibius are reported by hunters to seasonally move between the complex of protected areas of Togodo and its units.